Inclusive Governance Dalam Penanganan Anak Yang Kehilangan Orang Tua Akibat COVID-19 di Kota Pekanbaru - Rika Rani Sijabat; Dadang Mashur (Pusat Riset dan Inovasi Nasional, 2022)
Cases of death due to COVID-19 have also increased the number of children who have become orphans. Thus, these children are now in need of social welfare service (PPKS). Children who have lost their parents due to COVID-19 in Pekanbaru City are the highest compared to all regencies/cities in Riau Province, these children belong to a vulnerable group so that inclusiveness (partiality) is needed for them. This study aims to look at inclusive governance in handling children who have lost their parents due to COVID-19 in Pekanbaru city. This study uses qualitative research methods with descriptive nature. Data collection techniques were carried out by observation, interviews and documentation. The results showed that the handling of children who lost their parents due to COVID-19 in Pekanbaru City had fulfilled three elements of inclusive governance, namely transparency, participation, and equal treatment. However, in the implementation of the three elements of inclusive governance, there are still obstacles, namely changing policies and disproportionate assistance.